2020
DOI: 10.3389/fnbeh.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autonomous Sensory Meridian Response on the Functional Connectivity as Measured by Functional Magnetic Resonance Imaging

Abstract: Autonomous sensory meridian response (ASMR) is a sensory phenomenon in which audio-visual stimuli evoke a tingling sensation and is accompanied by a feeling of calm and relaxation. Therefore, there has been an increasing interest in using stimuli that elicit ASMR in cognitive and clinical neuroscience studies. However, neurophysiological basis of sensory-emotional experiences evoked by ASMR remain largely unexplored. In this study, we investigated how functional connectivity is changed while watching ASMR vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The study showed differences in brain activation between individuals who experience ASMR and those who do not ( Smith et al, 2017 ). Lee et al (2020) examined how functional connectivity changes during ASMR video viewing compared to resting state, and assessed its relevance to ASMR-induced emotional states. ASMR-induced changes in emotional state are negatively correlated with functional connectivity for visual information processing.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed differences in brain activation between individuals who experience ASMR and those who do not ( Smith et al, 2017 ). Lee et al (2020) examined how functional connectivity changes during ASMR video viewing compared to resting state, and assessed its relevance to ASMR-induced emotional states. ASMR-induced changes in emotional state are negatively correlated with functional connectivity for visual information processing.…”
Section: Introductionmentioning
confidence: 99%
“…K. Fredborg et al, 2021; M. Lee et al, 2019; Paszkiel et al, 2020; Pedrini et al, 2021; Seifzadeh et al, 2021; Swart, Banissy, et al, 2022; Tian et al, 2020) and fMRI studies (seven studies, S. Lee et al, 2020; Lochte et al, 2018; Sakurai et al, 2021; S.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, during ASMR stimulation, functional connectivity can apparently be altered between different brain areas (e.g., between the posterior cingulate cortex and the superior temporal gyrus; S. Lee et al, 2020), with increased functional connectivity being revealed when a seed-based analysis was used (S. Lee et al, 2020) and decreased functional connectivity when using an independent-components analysis technique (S.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of Psychology research on the subject can be seen in Swart et al (2021), Morales et al (2021), Roberts et al (2018Roberts et al ( , 2020Roberts et al ( , 2021, Janik & Osborne-Ford (2020), Cash et al (2018), as well as Fredborg et al (2017Fredborg et al ( , 2021. On the Neurosciences front, some notable works include Ohta & Inagaki (2021), Gyoung (2021), Maniago et al (2021), Idayati et al (2021), Fredborg et al (2021), Lee et al (2020), Smith et al (2020), Paszkiel et al (2020), Valtakari et al (2019), Poerio et al (2018), Lochte et al (2018), Barratt et al (2017), andSmith et al (2017). The Sonology field has also produced some recent works on ASMR, most notably Uchiyama & Kawamoto (2021), Klefeker et al (2020), Fukushima (2019), Kovacevich & Huron (2018), Janik & Banissy (2018), and Rouw & Erfanian (2018).…”
Section: What Is Asmr and How Is It Linkedmentioning
confidence: 99%